Law, government and authority in mid-Tudor England 1540-1570 - McComish, J (2013)
This thesis investigates legal and political authority in mid-Tudor England, using the operation of the legal system in Oxfordshire and Berkshire in the period from 1540 to 1570 as a case study through which to give context and content to more abstract forms of contemporary political thought. It seeks to address the broad question: how did people experience the civil—as opposed to the criminal—legal system, and what does this tell us about their understanding of authority? In so doing, it aims to shed light on mid-Tudor attitudes towards legality, limited government and the rule of law. The argument of the thesis is built up piece by piece. First, people in the Thames Valley engaged in a remarkable, and increasing, amount of litigation over the period in question, much of which was based on antecedent commercial transactions. Encountering the law, whether in its litigious or transactional forms, was thus a very common social experience. Second, despite their frequent interaction with the legal system, ordinary people perhaps knew less about the technical law than some historians have suggested. Third, even if technical legal knowledge was not widespread among the population, the complicated map of overlapping jurisdictions and rival legal institutions meant that ordinary people nonetheless cultivated a detailed mental map of their legal world. Boundaries mattered because jurisdiction and legal authority mattered. Fourth, partly because of their own lack of detailed technical knowledge, and partly because of the complicated legal landscape which they had to navigate, people sought out legal advice from professional advisers. Fifth, even if people frequently sought out professional legal advice, many people’s experience of the law (and of lawyers) was far more negative than their desire to seek out such advice might suggest. Seen in this light, the social utility of legal institutions was quite separate from their ability to provide an idealised standard of abstract justice.